Extracellular vesicles as mediators of stress response in embryo-maternal communication - Mousavi, Seyed Omid; Reshi, Qurat Ul Ain; Godakumara, Kasun; Kodithuwakku, Suranga; Fazeli, Alireza (Frontiers in Cell and Developmental Biology, 2024)
The pivotal role of extracellular vesicles (EVs) in facilitating effective communication between the embryo and maternal cells during the preimplantation stage of pregnancy has been extensively explored. Nonetheless, inquiries persist regarding the alterations in EV cargo from endometrial cells under stress conditions and its potential to elicit specific stress responses in trophoblast cells. Thus, the aim of this study was to elucidate the involvement of EV miRNA miRNAs in transmitting stress signals from maternal cells to trophoblasts. The receptive endometrial epithelium analogue RL95-2 cells were subjected to stress induction with 200 µM CoCl2 for 24 hours before EV isolation. JAr trophoblast spheroids, which serve as embryos, were subjected to treatment with stressed or unstressed EVs derived from RL95-2 cells for 24 hours. Transcriptomic alterations in the treated JAr spheroids as well as in the untreated group, as a negative control, were investigated by mRNA sequencing. Furthermore, the changes in EV miRNAs were assessed by sequencing EV samples. A comprehensive analysis comparing the miRNA profiles between stressed and unstressed EVs revealed significant changes in 25 miRNAs. Furthermore, transcriptomic analysis of JAr spheroids treated with stressed RL95-2 EVs versus unstressed EVs or the untreated group demonstrated 6 and 27 differentially expressed genes, respectively. Pathway enrichment analysis showed that stressed EVs induce alterations in gene expression in trophoblast cells, which is partially mediated by EV microRNAs. Our results suggest that EVs can transfer stress signals from endometrial cells to the embryo. These discoveries shed new light on the mechanism underlying implantation failures under stress conditions. Unraveling the role of EVs in transmitting stress signals, can extend our knowledge to pave the way for targeted interventions to manage stress-related implantation failures.